Acoustic Wave Propagation Patterns in the Ocean Column - Fachri Ali Badihi; Sri Pujiyati; Ayi Rahmat; Steven Solikin; Muhammad Hisyam (Politeknik Kelautan dan Perikanan Dumai, 2022)
Temperature and salinity play a role in the speed of sound and the process of sound propagation of acoustic waves in the water. Research on the propagation of sound waves in the ocean is a very interesting topic to do because it has many applications, including in underwater wireless communication systems and maritime security. This study aimed to analyze the propagation of acoustic waves in different water depths. The modeling was carried out with flat wave characteristics, in which the bathymetry characteristics of the seawater were ignored. In this ray path simulation, the frequency of 5.3Hz was used at 3 stations with different seawater depths in the Makassar Strait using temperature and salinity data downloaded from marine.coperniccus.eu data. The movement pattern of the acoustic waves was simulated using the Bellhop method. The ray tracing simulation results showed significant differences at the three locations. This was influenced by several factors, including the condition of the seawater environment, the placement of the transducer, the speed of sound, and the depth. Shallow seawater would show a more complicated ray path than deep seawater. The greater the angle of the half beam used, the greater the distance of the range of each beam of light will be so that the reflection of the resulting beam of light covers each column of seawater. The closer the distance between the resulting ray paths, the smaller the energy lost.